NMDA Receptor-Mediated Motor Cortex Plasticity After 20 Hz Transcranial Alternating Current Stimulation. (10th July 2018) - Wischnewski, M; Engelhardt, M; Salehinejad, M A; Schutter, D J L G; Kuo, M -F; Nitsche, M A
Abstract: Transcranial alternating current stimulation (tACS) has been shown to modulate neural oscillations and excitability levels in the primary motor cortex (M1). These effects can last for more than an hour and an involvement of N -methyl-d -aspartate receptor (NMDAR) mediated synaptic plasticity has been suggested. However, to date the cortical mechanisms underlying tACS after-effects have not been explored. Here, we applied 20 Hz beta tACS to M1 while participants received either the NMDAR antagonist dextromethorphan or a placebo and the effects on cortical beta oscillations and excitability were explored. When a placebo medication was administered, beta tACS was found to increase cortical excitability and beta oscillations for at least 60 min, whereas when dextromethorphan was administered, these effects were completely abolished. These results provide the first direct evidence that tACS can induce NMDAR-mediated plasticity in the motor cortex, which contributes to our understanding of tACS-induced influences on human motor cortex physiology.